Effectiveness and safety of electric heating moxibustion for perennial allergic rhinitis: A pilot, randomized, assessor-blind trial. (September 2022) - Jo, Hyo-Rim; Sung, Won-Suk; Jung, Chan-Yung; Lim, Chi-Yeon; Lee, Seung-Deok; Hong, Seung-Ug; Kim, Kyung-Ho; Kim, Eun-Jung
Abstract: Background: The prevalence of allergic rhinitis (AR), an inflammatory disease, is gradually increasing. Studies have reported that moxibustion is effective for treating AR. Electric heating moxibustion (EM) was developed to offer adaptable heat stimulation without the generation of smoke. Objectives: The objective of this study was to examine the possibility of EM in treating perennial allergic rhinitis (PAR) and to assess the feasibility of using this technique on a larger scale by comparing EM with acupuncture (AC). Design: A randomized pilot study was conducted on 40 patients with PAR. Patients were randomly assigned to one of two treatment groups: EM or AC. The primary outcome measure was the change in the total nasal symptom score (TNSS) between before and after treatment. The secondary outcome measures were the changes in the rhinoconjunctivitis quality of life questionnaire (RQLQ), nasal endoscopy index for pattern identification, pattern identification questionnaire for AR, total serum immunoglobulin E (IgE), eosinophil count, and adverse effects (AEs). Results: The results showed a statistically significant improvement in mean TNSS and RQLQ scores in both groups (p < 0.05), but no significant difference between the two groups. However, mean changes in itching and sneezing TNSS were significantly higher in the AC group. There was no significant difference in total serum IgE or eosinophil count before versus after treatment, nor was there any significant difference of three pattern subgroups between the two groups in the mean TNSS change. While the AC group reported two treatment-related AEs, there were no treatment-related AEs in the EM group. Conclusion: This trial provides evidence that EM isa safe alternative treatment for patients with PAR. Trial registration: ClinicalTrials.gov, NCT03342105. Registered on 14 November 2017. Highlights: Electric heating moxibustion treatment reduce symptoms and promoted quality of life of perennial allergic rhinitis patients. No treatment-related adverse events were reported in the electric heating moxibustion group. Our findings suggest that electric heating moxibustion can be considered as a safe alternative treatment.